2017
DOI: 10.1126/science.aah4390
|View full text |Cite
|
Sign up to set email alerts
|

On the deep-mantle origin of the Deccan Traps

Abstract: The Deccan Traps in west-central India constitute one of Earth's largest continental flood basalt provinces, whose eruption played a role in the Cretaceous-Paleogene extinction event. The unknown mantle structure under the Indian Ocean at the start of the Cenozoic presents a challenge for connecting the event to a deep mantle origin. We used a back-and-forth iterative method for time-reversed convection modeling, which incorporates tomography-based, present-day mantle heterogeneity to reconstruct mantle struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…Earlier, a model of shallow mantle melting in which the preexisting rift zones were reactivated and magma simply poured out of the fissures was proposed (Chandrasekharam & Parthasarathy, ). However, the possibility of the center of the plume head residing at the junction of Cambay and Narmada rifts could be explained based on the hypothesis that heat is also conducted into the adjacent mantle (Cambay and Saurashtra) as the plume rises (Campbell, ), supported by the results from time reversed convection modelling (Glišović & Forte, ). The present study thus supports the theory proposed by White and McKenzie () and Campbell and Griffiths () that a mantle plume was mainly responsible for the widespread volcanic activity in northwestern India and the trace of the plume passed through the Cambay Basin to the gulf of Cambay (near the junction of Cambay and Narmada rifts).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Earlier, a model of shallow mantle melting in which the preexisting rift zones were reactivated and magma simply poured out of the fissures was proposed (Chandrasekharam & Parthasarathy, ). However, the possibility of the center of the plume head residing at the junction of Cambay and Narmada rifts could be explained based on the hypothesis that heat is also conducted into the adjacent mantle (Cambay and Saurashtra) as the plume rises (Campbell, ), supported by the results from time reversed convection modelling (Glišović & Forte, ). The present study thus supports the theory proposed by White and McKenzie () and Campbell and Griffiths () that a mantle plume was mainly responsible for the widespread volcanic activity in northwestern India and the trace of the plume passed through the Cambay Basin to the gulf of Cambay (near the junction of Cambay and Narmada rifts).…”
Section: Discussionmentioning
confidence: 98%
“…:43°E at 67.5 Ma) northeast of the Reunion plume, which would have acted as a secondary source to the widespread Deccan flood basalt eruption. Globally, mantle plumes including the Reunion are seismically imaged in the form of low‐velocity conduits in the upper mantle (e.g., Glišović & Forte, ; Zhao, ). Consistent with the plume theory, we are able to recognize a prominent zone of low Vs in the upper mantle beneath the Cambay, Saurashtra, KSZ and along Western Ghats, down to a depth of 220 km (maximum depth of present investigation; Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been proposed by Glišović and Forte []—who reconstruct large‐scale plume and mantle structures in the past based on present‐day seismic tomography in contrast to the forward modeling approach and much higher resolved plume in this study (due to a considerably smaller model domain and the adaptive mesh refinement)—that the northern part of the Deccan Traps was generated by an additional unrecognized plume underneath the Comoros. Since this study is not designed to handle melting in continental environments, a second plume beneath India around 65 Ma would likely result in additional flow toward thinner oceanic lithosphere (regardless of a correct plume timing and position as discussed above).…”
Section: Discussionmentioning
confidence: 99%
“…A best fit between observational and model fields is then sought by minimising the regularisation parameter. Glišović & Forte (2014) and Glišović & Forte (2017) utilise this technique in global models to investigate regional evolution dynamics over the previous 70 Myr. In Glišović & Forte (2014), the QRV method is tested on a known data source, with the accuracy of the QRV predictions observed to begin falling away beyond 45 Myr.…”
Section: Discussionmentioning
confidence: 99%
“…The error levels up to 70 Ma are determined to be acceptable however, allowing the authors to investigate the evolution of Earth over the entire Cenozoic. In Glišović & Forte (2017) the QRV method is applied to observational data to investigate the evolution of upwellings in the Indian ocean. With the time intervals over which these QRV studies can reliably be calculated over falling broadly in line with the results shown here, choosing either the adjoint or QRV method can be argued from both sides.…”
Section: Discussionmentioning
confidence: 99%